2011
DOI: 10.4028/www.scientific.net/amr.282-283.702
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Flow at Water Jacket of an Internal Combustion Engine

Abstract: With the increasing degree of the enhancement of engine, engine cooling system design is considered particularly important. This paper used an established three-dimensional model of an engine water jacket to study, and used UDF function in the two-phase flow of the CFD, describe the mathematical model and simulation the engine at different operating conditions, and get the water jacket flow rate transfer thermal process. Finally, the results of the relationship between the engine water jacket of boiling heat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…[64][65][66] It not only significantly improves the feasibility and reliability of engine cooling performance prediction, but also reduces a lot of simulation trail time, algorithm optimization time and experimental verification time, and decreases the cost of prototype production in repeated experiments. [67][68][69][70][71] Comparing with other works, Zhang et al 72 used 3D simulation to analyze flow performance of water jacket and give evaluation references for designers. Yang et al 73 conducted heat transfer analysis of exhaust manifold with water jacket and showed that flow distribution is significantly related to heat transfer.…”
Section: Summary For Coolant Transport Analysis Methods Applied In Tw...mentioning
confidence: 99%
“…[64][65][66] It not only significantly improves the feasibility and reliability of engine cooling performance prediction, but also reduces a lot of simulation trail time, algorithm optimization time and experimental verification time, and decreases the cost of prototype production in repeated experiments. [67][68][69][70][71] Comparing with other works, Zhang et al 72 used 3D simulation to analyze flow performance of water jacket and give evaluation references for designers. Yang et al 73 conducted heat transfer analysis of exhaust manifold with water jacket and showed that flow distribution is significantly related to heat transfer.…”
Section: Summary For Coolant Transport Analysis Methods Applied In Tw...mentioning
confidence: 99%